A rare case of neonatal colonic obstruction caused by a solitary intestinal tumor - Yu Sugai; Yutaka Hirayama; Yasushi Iinuma; Kengo Nakaya; Takato Aikou; Shotaro Taki; Hideki Hashidate; Yoshiaki Kinoshita (Surgical Case Reports)
Abstract Background Intestinal obstruction caused by a tumor is very rare in newborns, and the preoperative diagnosis is difficult. We herein report a rare case of neonatal colonic obstruction due to solitary intestinal myofibroma with characteristic findings on gastrografin enema and the surgical strategy. Case presentation A 4-day-old female infant presented to our neonatal intensive-care unit with abdominal distention and bilious vomiting after feeding. A gastrografin enema showed that the transverse colon near the hepatic flexure was not delineated at the oral side. When pressure was applied, a small amount of contrast material moved into the mouth in the form of threads. Microcolon was not observed, and stenosis of the transverse colon was found 9 cm from the Bauhin valve. Partial resection and end-to-end anastomosis were performed. A pathological examination of the resected specimen suggested gastrointestinal stromal tumor (GIST). After obtaining a second opinion, the histology and immunohistological markers were deemed characteristic of infantile myofibroma. Conclusion If string sign and a napkin ring appearance are found in a case of neonatal intestinal obstruction, surgery should be performed with a tumor in mind. In cases of neonatal intestinal obstruction caused by a tumor, the lesion should be resected with a sufficient surgical margin before the pathological examination.